The Future of Nursing: Monitoring the Progress of Recommended Change in Hospitals, Nurse-Led Clinics, and Home Health and Hospice Agencies. (February 2015) - Pittman, Patricia; Bass, Emily; Hargraves, John; Herrera, Carolina; Thompson, Pamela
Abstract : OBJECTIVE: The objective of this study was to assess the implementation of recommendations of the Institute of Medicine (IOM) report, The Future of Nursing: Leading Change, Advancing Health . BACKGROUND: In 2010, the IOM made a series of recommendations aimed at transforming the role of nurses in healthcare delivery. METHODS: We conducted a multiyear survey, in 2011 and 2013, with nurse leaders who were members of the American Organization of Nurse Executives, the National Nursing Centers Consortium, or the Visiting Nurses Association of America. RESULTS: When comparing 2013 to 2011, we find progress in instituting the IOM's recommendations in 3 areas: (1) raising the proportion of employed RNs with at least a bachelor's degree; (2) expanding the proportion of healthcare institutions with nurse residency programs; and (3) offering opportunities for continuing nurse education CONCLUSIONS: Our findings suggest that healthcare organizations are transforming to support the recommendations of the IOM.